Pancasila and Various Actual Problems - Yudhanti, Ristina (Law Research Review Quarterly, 2016)
Pancasila is a view of life and philosophy of the Indonesian people which had once been replaced by the heart of the people of Indonesia by understanding other ideologies. Pancasila is a view of life that has Godhead, which means that humans are creatures who are obliged to believe and worship Him. Pancasila upholds humanity, justice, unity, unity, harmony, harmony and balance. Pancasila is accommodating and follows a democratic government system based on deliberation and consensus policies. Pancasila is practiced through national development in four fields of politics, economy, social culture and defense and security. By exploring the noble values of Pancasila, of course we are aware and confident of the superiority of Pancasila.